Design and implementation of Smart Agriculture using Embedded System (International Journal of Engineering and Computer Science, 2016)
A smart way of automating farming process can be called as Smart Agriculture. By implying an automated system we can eliminate possible threats to the crops by reducing the human intervention. The major emphasize will be on providing favorable atmosphere for plants. These agricultural automated systems will help in managing and maintain safe environment especially the agricultural areas. Environment real time monitoring is an important factor in smart farming.